Had Al-Kifayah: A Guide to Determining Asnaf of The Fakir and The Poor - Anggoro Sugeng; Nur Sya'adi (Maqrizi: Journal of Economics and Islamic Economics, 2022)
Had al-Kifayah is a standard of living/standard of adequacy to live a decent life in the perspective of Islamic economics. A person with a daily life below the standard of had al-kifayah is included in the category/ asnaf of the poor. This article aims to describe the had al-kifayah indicators as a guide in determining asnaf indigent and poor. This research is a literature study, by looking at the literature from several researchers who highlight from various perspectives and different views. The results of this study indicate that the had al-kifayah indicators consisting of food and drink, clothing, housing, education, health, and vehicles are in accordance with the rules of maqasid ash-shari'ah which can ensure the realization of a decent life. Had al-kifayah does not only look at the amount of income, but also guarantees the fulfillment of indicators for the needs of a decent life so that it can change the status that was initially lacking to become affluent in the future.